Objective assessment of vitiligo with a computerised digital imaging analysis system - Shamsudin, Norashikin; Hussein, Suraiya; Nugroho, Hermawan; Ahmad Fadzil, Mohd Hani (Wiley-Blackwell Publishing Asia, 2015)
An objective tool to quantify treatment response in vitiligo is currently lacking. This study aimed to objectively evaluate the treatment response in vitiligo by using a computerised digital imaging analysis system (C-DIAS) and to compare it with the physician's global assessment (PGA). Tacrolimus ointment 0.1% (Protopic; Astellas Pharma Tech,Toyama, Japan) was applied twice daily on selected lesions which were photographed every 6 weeks for 24 weeks. The primary efficacy end-point was the mean percentage of repigmentation (MPR), as assessed by the digital method (MPR-C-DIAS) or by the PGA. The response was categorised into none (0%), mild (1–25%), moderate (26–50%), good (51–75%) and excellent (76–100%). MPR-C-DIAS: Out of 56 patients, 44 (79%) responded. Overall, the response was mild in 22 (39%), moderate in 21(40%) and good in one (2%) patient(s). A total of 39 (70%) patients responded as measured by PGA. The repigmentation was mild in 27(48%), moderate in 10 (18%) and good to excellent in two (4%) patients. The κ test of consistency was 0.17 (P = 0.053), which shows poor agreement between the two assessment methods, although this is not statistically significant. The C-DIAS can be used to perform an objective analysis of repigmentation or depigmentation in vitiligo skin lesions in response to treatment.